ANALISIS KOMPARATIF BAHASA PEMROGRAMAN UNTUK PEMULA IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Wibowo, Herlan; Faisal Ilham, Muhammad; Albani, Taufik Eka; Fawwauzy, Zacky Rafian; Anshor, Abdul Halim Anshor (JTIK (Jurnal Teknik Informatika Kaputama), 2025)
Selecting the right programming language for beginners is a significant challenge in software development. This research aims to analyze a comparison of programming languages Python, JavaScript, Java, C++, and PHP using the Simple Additive Weighting (SAW) method to provide an objective recommendation for beginners. The evaluation is based on six key criteria: ease of learning, job opportunities, execution speed, versatility, community & ecosystem, and maintenance cost, with weights assigned according to the importance of each criterion. Data were obtained through literature review, user surveys, and expert judgment analysis. The results show that Python received the highest preference score (1.13), followed by JavaScript (1.08), Java (1.18), C++ (1.27), and PHP (1.34). Python excelled in terms of ease of learning and versatility, while JavaScript led in community and ecosystem aspects. The study concludes that Python is the most suitable programming language for beginners, especially for foundational learning and general application development. These findings have implications for the development of programming curricula and recruitment strategies in the information technology industry.